Exosome-shuttled miR-150–5p from LPS-preconditioned mesenchymal stem cells down-regulate PI3K/Akt/mTOR pathway via Irs1 to enhance M2 macrophage polarization and confer protection against sepsis - Zheng, Ting; Li, Sipeng; Zhang, Teng; Fu, Wei; Liu, Shuchang; He, Yuxin; Wang, Xiao; Ma, Tao (Frontiers in Immunology, 2024)
Rationale: Sepsis is a life-threatening organ dysfunction and lack of effective measures in the current. Exosomes from mesenchymal stem cells (MSCs) reported to alleviate inflammation during sepsis, and the preconditioning of MSCs could enhance their paracrine potential. Therefore, this study investigated whether exosomes secreted by lipopolysaccharide (LPS)-pretreated MSCs exert superior antiseptic effects, and explored the underlying molecular mechanisms.Methods: Exosomes were isolated and characterized from the supernatants of MSCs.The therapeutic efficacy of normal exosomes (Exo) and LPS-pretreated exosomes (LPS-Exo) were evaluated in terms of survival rates, inflammatory response, and organ damage in an LPS-induced sepsis model. Macrophages were stimulated with LPS and treated with Exo or LPS-Exo to confirm the results of the in vivo studies, and to explain the potential mechanisms.Results: LPS-Exo were shown to inhibit aberrant pro-inflammatory cytokines, prevent organ damages, and improve survival rates of the septic mice to a greater extent than Exo. In vitro, LPS-Exo significantly promoted the M2 polarization of macrophages exposed to inflammation. miRNA sequencing and qRT-PCR analysis identified the remarkable expression of miR-150-5p in LPS-Exo compared to that in Exo, and exosomal miR-150-5p was transferred into recipient macrophages and mediated macrophage polarization. Further investigation demonstrated that miR-150-5p targets Irs1 in recipient macrophages and subsequently modulates macrophage plasticity by down-regulating the PI3K/Akt/mTOR pathway.The current findings highly suggest that exosomes derived from LPS preconditioned MSCs represent a promising cell-free therapeutic method and highlight miR-150-5p as a novel molecular target for regulating immune hyperactivation during sepsis.